Risk of cardiovascular mortality in patients with gastric cancer - Tian Zhang; Lingling Guan; Xiaomeng Xie; Juecai Chen; Dongjing Ni (PLoS ONE, 2025)
Purpose To assess the excess cardiovascular disease (CVD) mortality risk in patients with gastric cancer (GC) compared with the general population. Methods Using data from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) program, we conducted a retrospective, population-based cohort study of 41,083 GC patients ≥30 years old between January 1, 1990, and December 31, 2021. A reference cohort from the corresponding general population was also included. Incidence rate ratios (IRRs) for CVD mortality were estimated using Poisson regression. Results GC patients were associated with a higher risk of CVD mortality relative to the general population (IRR: 1.46; 95% CI: 1.40–1.52). The relative risk was highest among younger patients aged 30–39 years (IRR: 7.69; 95% CI: 2.48–23.86). Cardiovascular mortality risk peaked during the first month after cancer diagnosis (IRR: 11.52; 95% CI: 9.97–13.31). The relationship between GC and CVD mortality varied according to demographic and clinical characteristics. Conclusions These population-based findings support early cardiac assessment and comprehensive risk stratification in GC care. Prospective studies with richer confounder data are needed to test whether these strategies improve outcomes.